1995
DOI: 10.1128/aac.39.10.2345
|View full text |Cite
|
Sign up to set email alerts
|

NP-06: a novel anti-human immunodeficiency virus polypeptide produced by a Streptomyces species

Abstract: From an extract of a Streptomyces culture, we identified and purified a novel compound, NP-06, which is active against human immunodeficiency virus (HIV) in vitro. Analyses indicate that NP-06 is a hydrophobic 21-mer oligopeptide, N terminally cyclized through the side chain of Asp-9, containing two intramolecular cystine linkages with a molecular weight of 2,163.4. The 50% inhibitory concentrations were 2.8 and 1.3 M when NP-06 was tested for in vitro anti-HIV-1 activity in ATH8 cells and phytohemagglutinin-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…The target molecule of siamycins in anti-HIV activity has been proposed to be HIV envelope glycoprotein gp41 because siamycins have a strong inhibitory effect on syncytium formation and exhibit sequence similarity to part of gp41 (7,11,18). However, unlike the sequence similarity between siamycin and gp41, there is no sequence similarity between siamycin I and GBAP.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The target molecule of siamycins in anti-HIV activity has been proposed to be HIV envelope glycoprotein gp41 because siamycins have a strong inhibitory effect on syncytium formation and exhibit sequence similarity to part of gp41 (7,11,18). However, unlike the sequence similarity between siamycin and gp41, there is no sequence similarity between siamycin I and GBAP.…”
Section: Discussionmentioning
confidence: 77%
“…Mass spectrometry suggested that the molecular mass of this compound was 2,164, which is identical to the molecular masses of siamycin I (14, 61), NP-06 (7), and RP-71955 (18). These compounds were previously screened for anti-human immunodeficiency virus (HIV) activity and are known to have antimicrobial activity against gram-positive bacteria as well (7,18,30,61). They were found to be tricyclic peptides consisting of 21 amino acids.…”
Section: Resultsmentioning
confidence: 99%
“…Chokekijchai et al (9) screened 9,000 extracts of bacterial samples from various sources for anti-HIV activity. A crude extract of strain SKH-2344, a Streptomyces strain isolated from soil, showed high anti-HIV activity.…”
Section: Discussionmentioning
confidence: 99%
“…7), from Streptomyces have been described: siamycin II (RP 71955, BMY 29303), 22±24 NP-06 (FR 901724) 25,26 and siamycin I (BMY-29304). 24,27 They differ from one another only at position 4 (Val or Ile) or 17 (again, Val or Ile), which should not make much of a difference in terms of conformational or functional properties.…”
Section: S I a M Y C I N Smentioning
confidence: 99%
“…The siamycins have been found to inhibit HIV infection in vitro; they exert a strong inhibitory effect on syncytium formation while only weakly inhibiting virus-cell binding. 25,26 The most likely target for the mode of action of siamycins is the HIV envelope glycoprotein gp41. 24 In fact, 33% sequence identity was observed between siamycin II and residues 608±628 of gp41 (amino acid numbering for the gp160 precursor).…”
Section: S I a M Y C I N Smentioning
confidence: 99%